Clinical study of role of ultrasound in first trimester vaginal bleeding - K., Sandyashree P.; C. V., Swathi Nayak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Vaginal bleeding is a serious cause which needs an emergency consultation. Major causes are abortion, ectopic pregnancy and molar pregnancy others like cervical erosion, polyp and carcinoma. The objective is to identify cause, assess the prognosis and institute appropriate management. Methods: Prospective study in MMC and RI, OBG, Mysore from November 2015 to September 2017. General physical and pelvic examination done for provisional clinical diagnosis and subjected to Ultrasound. Clinical diagnosis and ultrasound diagnosis were correlated. Results: 100 cases of first trimester bleeding evaluated by Ultrasonography with an incidence 2.37%. Most common cause was abortion (81.6%) then molar (10%) and ectopic pregnancy (9%). Out of 100 cases, 72 cases confirmed, 28 cases proved by ultrasound which was misdiagnosed on clinical examination with disparity of 72 between clinical and ultrasound diagnosis. 13 cases viable pregnancy by ultrasonography with sensitivity, specificity, NPV and PPV of 100% and 69 cases nonviable pregnancies with sensitivity, specificity and NPV of 100%. 9 cases ectopic pregnancy were diagnosed on ultrasound with sensitivity 100%, specificity 98.9%, PPV 99% and accuracy 99%. Clinical diagnosis in diagnosing viable pregnancies has sensitivity 76.92%, specificity 64.36% and PPV 24.39%. In diagnosis nonviable pregnancies, clinical diagnosis, poor statistical correlation with sensitivity 77.58, specificity 83.33%, PPV 86.53% and NPV 72.91%. Ultrasonographic diagnosis proved as very accurate on statistical correlation. Conclusions: Ultrasound is sensitive, cost effective and non-invasive diagnostic tool in first trimester bleeding. In this study, it helped in correct diagnosis of clinically misdiagnosed cases apart from confirming the diagnosis in others.